1989
DOI: 10.1159/000125121
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Luteinizing Hormone-Releasing Hormone Release from the Mediobasal Hypothalamus of Ovariectomized, Steroid-Primed Middle-Aged Rats as Measured by Push-Pull Perfusion

Abstract: The spontaneous luteinizing hormone (LH) surge on proestrus as well as the steroid-induced LH surge and hypersecretion of LH following ovariectomy are attenuated in middle-aged female rats when compared to their young counterparts. It is generally assumed that the lower titers of serum LH measured in aging animals result, in part, from age-related alterations in luteinizing hormone-releasing hormone (LHRH) neurosecretion, yet no direct measurements of LHRH release from the hypothalamus of aging females are cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 18 publications
5
39
0
1
Order By: Relevance
“…The decreased LHRH release was also supported by the slow and low increase in plasma LH after progesterone treatment in old females. Rubin et al(1989) recently observed with the push-pull perfusion technique that the mean levels of LHRH in perfusates in estrogen and progesteronetreated middle-aged females (10-12 months) were lower than those in young females. If, similarly to their rats, less LHRH was released from the ME to the portal circulation in our old rats, a difference between the plasma LH concentrations in the two age groups would result.…”
Section: Discussionmentioning
confidence: 98%
“…The decreased LHRH release was also supported by the slow and low increase in plasma LH after progesterone treatment in old females. Rubin et al(1989) recently observed with the push-pull perfusion technique that the mean levels of LHRH in perfusates in estrogen and progesteronetreated middle-aged females (10-12 months) were lower than those in young females. If, similarly to their rats, less LHRH was released from the ME to the portal circulation in our old rats, a difference between the plasma LH concentrations in the two age groups would result.…”
Section: Discussionmentioning
confidence: 98%
“…Using age-appropriate rats at young, middle-aged, and old ages, we ovariectomize the animals, wait 1 month, and then give ET (i.e., estradiol), with or without progestins, in physiologically relevant dosages Yin and Gore, 2006). Another important difference between primates and rodents is that postmenopausal increases in GnRH or surrogates for GnRH (e.g., gonadotropins or gonadotropin-free a subunit) occur during the perimenopause (Hall and Gill, 2001;Maffucci and Gore, 2006), whereas in rodents, GnRH neurosecretion and the preovulatory GnRH/LH surge declines at estropause (Rubin and Bridges, 1989).…”
Section: Patterns Of Reproductive Senescence Differ Across Speciesmentioning
confidence: 99%
“…(2) Acyclic old rats can be induced to ovulate by neurochemical, hormonal, or social stimuli (for review, see Gore, 2001). (3) Pulsatile GnRH release decreases in middle-aged rats (Rubin and Bridges, 1989) and increases in perimenopausal rhesus monkeys . Although there are species differences in these phenomena, both of these changes precede actual reproductive failure.…”
Section: The Circuitry Driving Gnrh Neurons Undergoes Age-related Chamentioning
confidence: 99%
“…It should be noted that additional changes in GnRH activity have been reported by investigators who have utilized rats that have reached more advanced stages of reproductive senescence, particularly during times of increased demand on the population of GnRH neurons. These changes include decreased in vivo output of GnRH in conjunction with the steroidinduced LH surge using push-pull perfusion (Rubin and Bridges, 1989) and decreased LH pulse frequency and amplitude in ovariectomized rats (Scarbrough FIG. 1.…”
Section: Changes In the Pattern Of Gonadotropin Secretion Reflecmentioning
confidence: 99%